Chlamydia pneumoniae Polioencephalomyelitis and Ganglionitis in Captive Houston Toads (Anaxyrus houstonensis). Issue 5 (September 2019) - Fratzke, Alycia; Howard, Lauren L.; Tocidlowski, Maryanne E.; Armién, Anibal; Oliveira, Fabiano; Ritchie, Branson; Berlin, Erin; Snook, Eric
Chlamydia pneumoniae is a ubiquitous pathogen causing disease in humans, mammals, birds, reptiles, and amphibians. Since 2012, C. pneumoniae infection has caused neurologic disease and mortality in a breeding colony of endangered Houston toads ( Anaxyrus houstonensis ) at the Houston Zoo. The purpose of this report is to present the histopathologic and ultrastructural characteristics of C. pneumoniae infection in Houston toads. Fourteen cases were evaluated by histopathology and 1 case was evaluated by electron microscopy. The major histopathologic finding was necrotizing and histiocytic polioencephalomyelitis and ganglionitis. Bacteria formed intracytoplasmic inclusions within neurons but frequently extended into the surrounding tissue from necrotic cells. Ultrastructural evaluation showed the bacteria formed reticulate and elementary bodies characteristic of Chlamydia spp .